Flame-retardant stone plastic floor and preparation method thereof

By adopting layered design in stone plastic flooring and using different layers of flame retardant materials to form a collaborative flame retardant system, the problem of poor flame retardant performance of traditional stone plastic flooring is solved, and the flame retardant performance and durability of the floor are significantly improved.

CN119593559AActive Publication Date: 2025-03-11GUANGDONG NATURE HOME FURNISHING TECH RES CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411796265.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-11
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Traditional stone plastic floors have poor flame retardant performance, are flammable and easily wearable, making it difficult to meet fire safety and durability requirements.

Method used

The layered design is adopted, and the surface layer, intermediate layer and cladding layer contain flame retardant, aluminum hydroxide and ammonium polyphosphate respectively to form a coordinated flame retardant system to improve the flame retardant effect of the floor.

Benefits of technology

It effectively improves the flame retardant performance of the floor, reduces fire risk, and enhances wear resistance and UV resistance, extending the service life of the floor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593559A_ABST
    Figure CN119593559A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of stone-plastic floors, in particular to a flame-retardant stone-plastic floor and a preparation method thereof.The flame-retardant stone-plastic floor comprises a base layer, a middle layer, a surface layer and a coating layer, the middle layer is arranged between the base layer and the surface layer, and the coating layer wraps the base layer, the middle layer and the surface layer; the base layer comprises 60-70 parts of polyvinyl chloride resin, 200-250 parts of calcium carbonate powder, 3-5 parts of a stabilizer and 1-2 parts of a lubricant; according to the scheme, the layers of the floor can play different flame-retardant functions through layered design, a synergistic flame-retardant system is formed, the flame retardant on the surface layer can play a role firstly when being in contact with flames, the flame spreading speed is slowed down, the aluminum hydroxide flame retardant on the middle layer is heated to decompose and absorb a large amount of heat, release water vapor and dilute oxygen concentration, and the flame-retardant effect is achieved. And the ammonium polyphosphate flame retardant of the outer wrapping layer further obstructs flames, the flame retardant effect of the floor can be effectively improved through the layered flame retardant design, and the risk of fire disasters is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stone plastic flooring, and in particular to a flame retardant stone plastic flooring and a preparation method thereof. Background Art

[0002] With the continuous development of the building decoration industry, people's requirements for floor materials are increasing. Among the many types of floors, stone plastic floors have attracted widespread attention due to their aesthetics, economy and ease of installation. However, traditional stone plastic floors have obvious deficiencies in flame retardant properties. When a fire occurs, it is easy to become a medium for the spread of fire, posing a serious threat to the safety of life and property.

[0003] In some crowded places such as shopping malls, hotels, schools and residences, the flame retardancy of floor materials is very important. Once a fire occurs, the flames, smoke and toxic gases produced by the burning of ordinary floors will not only accelerate the spread of the fire, but also hinder the evacuation of people and increase the risk of casualties. Therefore, the development of stone plastic flooring with excellent flame retardant properties has become an urgent problem to be solved in the industry.

[0004] At the same time, during the long-term use of the floor, its wear resistance and UV resistance need to be considered. Frequent movement of people and dragging of furniture will cause the floor surface to wear, affecting its appearance and service life. In areas with good indoor lighting or direct sunlight, ultraviolet radiation can easily cause the floor material to age and discolor, reducing its decorative effect and durability.

[0005] Therefore, the present invention proposes a flame-retardant stone plastic floor and a preparation method thereof. Through a layered design, each layer of the floor can play a different flame-retardant function to form a synergistic flame-retardant system. The flame retardant in the surface layer can play a role first when the flame contacts it, slowing down the spread of the flame. The aluminum hydroxide flame retardant in the middle layer decomposes under heat to absorb a large amount of heat and releases water vapor, diluting the oxygen concentration and preventing the continued combustion. The ammonium polyphosphate flame retardant in the outer wrapping layer further blocks the flame. This layered flame-retardant design can effectively improve the flame-retardant effect of the floor and greatly reduce the risk of fire. Summary of the invention

[0006] Technical problems to be solved: Traditional stone plastic flooring has poor flame retardancy and is easy to wear.

[0007] In view of the deficiencies in the prior art, the present invention provides a flame-retardant stone plastic floor and a preparation method thereof, thereby solving the technical problems mentioned in the background technology.

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides a flame-retardant stone plastic floor, the floor comprising a base layer, an intermediate layer, a surface layer and a covering layer, the intermediate layer is placed between the base layer and the surface layer, and the covering layer is wrapped around the outside of the base layer, the intermediate layer and the surface layer;

[0010] The base layer comprises 60-70 parts of polyvinyl chloride resin, 200-250 parts of calcium carbonate powder, 3-5 parts of stabilizer, and 1-2 parts of lubricant;

[0011] The middle layer contains 70-80 parts of non-crystalline copolyester and 20-30 parts of aluminum hydroxide flame retardant;

[0012] The surface layer comprises 70-80 parts of polyvinyl chloride resin, 10-15 parts of alumina wear-resistant agent, 5-8 parts of flame retardant, 1-2 parts of anti-ultraviolet agent, and 3-5 parts of stabilizer;

[0013] The coating layer contains 70-80 parts of thermoplastic polyurethane elastomer rubber and 20-30 parts of ammonium polyphosphate.

[0014] In a possible implementation, the stabilizer is a calcium zinc stabilizer, the lubricant is stearic acid, the flame retardant is antimony trioxide, and the anti-ultraviolet agent is benzotriazole.

[0015] In a second aspect, the present invention provides a method for preparing a flame retardant stone plastic floor, which is applied to the preparation of the flame retardant stone plastic floor, and comprises the following method steps:

[0016] Step 1: Base layer preparation:

[0017] The PVC resin, calcium carbonate powder, stabilizer and lubricant additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes according to the above ratio to make the materials evenly mixed;

[0018] Add the mixed materials into a single-screw or twin-screw extruder, set the temperature of each section of the extruder to 150-160°C, 160-170°C, 170-180°C, and control the screw speed at 30-50 rpm to extrude into sheets with a thickness of about 2-3mm, then cool and shape, and cut into suitable sizes for later use;

[0019] Step 2: Preparation of the intermediate layer:

[0020] After drying the PETG particles and the aluminum hydroxide flame retardant in a vacuum drying oven at 80-90°C for 4-6 hours, the PETG particles and the aluminum hydroxide flame retardant are melt-blended and extruded in a twin-screw extruder. The temperature of each section of the extruder is set to 200-210°C, 210-220°C, and 220-230°C. The screw speed is 200-300 rpm to form a sheet with a thickness of about 1-2 mm. After cooling, the sheet is cut into a suitable size for standby use.

[0021] Step 3: Surface preparation:

[0022] The PVC resin, aluminum oxide wear-resistant agent, flame retardant, UV-resistant agent, stabilizer additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes to make the materials evenly mixed;

[0023] The mixed material is extruded into a sheet in an extruder, the extruder temperature is set to 160-170°C, 170-180°C, 180-190°C, the screw speed is 40-60 rpm, the sheet thickness is about 0.5-1mm, cooled and shaped, and cut into suitable sizes for use;

[0024] Step 4: Preparation of wrapping layer:

[0025] Dry the TPU pellets in a vacuum drying oven at 80-90°C for 4-6 hours;

[0026] The dried TPU particles and ammonium polyphosphate powder are fully mixed in a high-speed mixer according to the ratio. The mixing time is about 10-15 minutes, and the speed is controlled at 800-1200 rpm;

[0027] The mixed materials are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion temperature is set at 180-220°C, and the screw speed is 200-300 rpm to obtain TPU / APP composite material particles;

[0028] The TPU / APP composite material particles are made into a film with a thickness of about 0.2-0.5 mm by a casting or blow molding process for later use;

[0029] Step 5: Floor molding:

[0030] After the prepared base layer, middle layer and surface layer are stacked in order, they are preliminarily hot-pressed and laminated on a hot press machine. The hot-pressing conditions are temperature 120-150°C, pressure 3-5MPa, and time 2-3 minutes, so that the three layers are tightly combined;

[0031] The prepared TPU / APP film is covered on the surface of the preliminarily compounded board, and then the pattern is hot-pressed again by a hot press at 130-160°C and a pressure of 4-6MPa for 3-5 minutes, so that the film is firmly wrapped around the outside of the floor, and a decorative and anti-slip pattern is formed, and finally a flame-retardant stone plastic floor product is obtained.

[0032] Beneficial effects compared with the prior art:

[0033] 1. In this scheme, through the layered design, each layer of the floor can play a different flame retardant function to form a synergistic flame retardant system. The flame retardant in the surface layer can play a role first when the flame contacts it, slowing down the spread of the flame. The aluminum hydroxide flame retardant in the middle layer decomposes under heat and absorbs a large amount of heat, and releases water vapor, diluting the oxygen concentration and preventing the continued combustion. The ammonium polyphosphate flame retardant in the outer wrapping layer further blocks the flame. This layered flame retardant design can effectively improve the flame retardant effect of the floor and greatly reduce the risk of fire.

[0034] 2. In this solution, by adding PETG material, PETG helps to evenly disperse the aluminum hydroxide flame retardant, so that the flame retardant can play a better role. At the same time, PETG itself has a certain ability to block heat transfer. During the spread of flames, it can form a heat insulation barrier to prevent heat from being transferred to other layers, thereby enhancing the flame retardant properties of the entire floor and enabling the floor to better meet fire safety requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.

[0036] Figure 1 This is a schematic diagram of the overall structure of a flame-retardant stone plastic floor;

[0037] Figure 2 The present invention is a process flow chart for preparing a flame retardant stone plastic floor. DETAILED DESCRIPTION

[0038] Preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the present invention can also be implemented in various forms, so the present invention is not limited to the embodiments described below.

[0039] The technical solution in the embodiment of the present application is to solve the problems of the above-mentioned background technology, and the overall idea is as follows:

[0040] Embodiment 1:

[0041] Please refer to Figure 1-Figure 2 As shown, this embodiment introduces a flame-retardant stone plastic floor, comprising a base layer 1, an intermediate layer 2, a surface layer 3, and a covering layer 4, wherein the intermediate layer 2 is placed between the base layer 1 and the surface layer 3, and the covering layer 4 is wrapped around the outside of the base layer 1, the intermediate layer 2, and the surface layer 3;

[0042] The base layer 3 is used for structural support, so that the floor has a certain degree of deformation resistance; the middle layer 2 is used to prevent heat transfer, forming a flame retardant barrier, and enhancing the overall flame retardant performance of the floor; the surface layer 1 is used for wear resistance and protection, so that the floor surface can withstand frequent friction such as people walking and furniture moving, reduce surface wear, and maintain the durability of the floor appearance; the coating layer 4 is used for protection and decoration, and can protect the internal base layer 1, middle layer 2, and surface layer 3 from erosion by the external environment, such as preventing the invasion of moisture, oil, etc. Through hot embossing pattern treatment, the coating layer 4 can form a decorative and anti-slip pattern, so that the floor not only meets safety requirements, but also has a good appearance effect, which increases the practicality and aesthetics of the floor.

[0043] Embodiment 2:

[0044] The embodiment of the present invention provides a flame-retardant stone plastic floor, comprising the following raw materials in parts by weight:

[0045] Base layer: 65 parts of polyvinyl chloride (PVC) resin, 230 parts of calcium carbonate powder, 4 parts of calcium zinc stabilizer, and 1.5 parts of stearic acid;

[0046] Middle layer: 75 parts of non-crystalline copolyester (PETG), 25 parts of aluminum hydroxide (ATH) flame retardant;

[0047] Surface layer: 75 parts of polyvinyl chloride (PVC) resin, 12 parts of alumina wear-resistant agent, 6 parts of antimony trioxide flame retardant, 1.5 parts of benzotriazole anti-ultraviolet agent, 4 parts of stabilizer;

[0048] Wrapping layer: 75 parts of thermoplastic polyurethane elastomer rubber (TPU), 25 parts of ammonium polyphosphate (APP);

[0049] The flame retardant stone plastic floor provided in this embodiment is prepared by the following method steps:

[0050] 1. Preparation of base layer: PVC resin, calcium carbonate powder, stabilizer and lubricant additive are fully mixed in a high-speed mixer at a speed of 900 rpm for 12 minutes according to the above ratio to make the materials evenly mixed. The mixed materials are added to a twin-screw extruder. The temperature of each section of the extruder is set to 155°C, 165°C and 175°C in sequence. The screw speed is controlled at 40 rpm to extrude into a sheet with a thickness of about 2.5 mm, then cooled and shaped, and cut into suitable sizes for standby use;

[0051] 2. Preparation of the middle layer: After drying the PETG particles and the aluminum hydroxide flame retardant in a vacuum drying oven at 85°C for 5 hours, they were melt-blended and extruded in a twin-screw extruder. The temperatures of each section of the extruder were set to 205°C, 215°C, and 225°C, and the screw speed was 250 rpm to form a sheet with a thickness of about 1.5 mm. After cooling, the sheet was cut into suitable sizes for standby use;

[0052] 3. Surface preparation: PVC resin, aluminum oxide wear-resistant agent, flame retardant, anti-ultraviolet agent, stabilizer additive are fully mixed in a high-speed mixer at a speed of 900 rpm for 12 minutes according to the proportion to make the materials evenly mixed. The mixed materials are extruded into sheets in an extruder. The extruder temperature is set to 165°C, 175°C, and 185°C, the screw speed is 50 rpm, and the sheet thickness is about 0.8mm. Cool and shape and cut into suitable sizes for standby use;

[0053] 4. Preparation of the wrapping layer: Dry the TPU particles in a vacuum drying oven at 85°C for 5 hours, fully mix the dried TPU particles and ammonium polyphosphate powder in a high-speed mixer according to the ratio, the mixing time is about 12 minutes, the speed is controlled at 1000 rpm, the mixed materials are added to a twin-screw extruder for melt blending and extrusion granulation, the extrusion temperature is set at 200°C, the screw speed is 250 rpm, and TPU / APP composite material particles are obtained. The TPU / APP composite material particles are made into a film with a thickness of about 0.3 mm by a casting process for standby use;

[0054] 5. Floor molding

[0055] After the prepared base layer, middle layer and surface layer are stacked in order, they are preliminarily hot-pressed and laminated on a hot press machine. The hot-pressing conditions are temperature 135°C, pressure 4MPa, and time 2.5 minutes, so that the three layers are tightly bonded.

[0056] The prepared TPU / APP film is covered on the surface of the preliminarily compounded board, and then subjected to hot pressing treatment again at 145°C and 5 MPa for 4 minutes, so that the film is firmly wrapped around the outside of the floor and a decorative and anti-slip pattern is formed, finally obtaining a flame-retardant stone plastic floor product.

[0057] Comparative Example 1:

[0058] The embodiment of the present invention provides a flame-retardant stone plastic floor, comprising the following raw materials in parts by weight:

[0059] Overall mixed materials: 70 parts of non-crystalline copolyester (PETG), polyvinyl chloride (PVC) resin (combining the dosage range of the base layer and the surface layer, about 65 parts can be taken), calcium carbonate powder (about 200 parts can be taken according to the dosage ratio of the base layer), 20 parts of aluminum hydroxide (ATH) flame retardant, aluminum oxide wear-resistant agent (about 8 parts can be taken according to the dosage ratio of the surface layer), flame retardant (such as antimony trioxide, about 4 parts can be taken according to the dosage ratio of the surface layer), anti-ultraviolet agent (such as benzotriazole, about 1 part can be taken according to the dosage ratio of the surface layer), stabilizer (combining the dosage range of the base layer and the surface layer, about 4 parts can be taken), lubricant (such as stearic acid, about 1 part can be taken according to the dosage ratio of the base layer), and 20 parts of ammonium polyphosphate (APP) are mixed;

[0060] The flame retardant stone plastic floor provided in this embodiment is prepared by the following method steps:

[0061] Mix all the above materials in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes to make the materials uniform;

[0062] The mixed materials are added into a single-screw or twin-screw extruder, and the temperature of each section of the extruder is set to 150-180°C (comprehensively considering the original base layer, middle layer and surface layer extruder temperature range), and the screw speed is controlled at 30-60 rpm (comprehensively considering the original screw speed range of each layer), and extruded into a sheet with a thickness of about 3-5mm (comprehensively considering the original thickness range of each layer), and then cooled and shaped, and cut into suitable sizes for use.

[0063] Comparative Example 2:

[0064] The embodiment of the present invention provides a flame-retardant stone plastic floor, comprising the following raw materials in parts by weight:

[0065] Base layer: 60 parts of polyvinyl chloride (PVC) resin, 200 parts of calcium carbonate powder, 3 parts of stabilizer (such as calcium zinc stabilizer), 1 part of lubricant (such as stearic acid);

[0066] Middle layer: 20 parts of aluminum hydroxide (ATH) flame retardant (PETG is removed, only the flame retardant component is retained);

[0067] Surface layer: 70 parts of polyvinyl chloride (PVC) resin, 10 parts of alumina wear-resistant agent, 5 parts of flame retardant (such as antimony trioxide), 1 part of anti-ultraviolet agent (such as benzotriazole), and 3 parts of stabilizer;

[0068] Outer wrapping layer: 70 parts of thermoplastic polyurethane elastomer rubber (TPU), 20 parts of ammonium polyphosphate (APP);

[0069] The flame retardant stone plastic floor provided in this embodiment is prepared by the following method steps:

[0070] 1. Preparation of base layer: PVC resin, calcium carbonate powder, stabilizer and lubricant additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes according to the above ratio to make the materials evenly mixed; the mixed materials are added to a single-screw or twin-screw extruder, and the temperature of each section of the extruder is set to 150-160°C, 160-170°C, and 170-180°C in sequence, and the screw speed is controlled at 30-50 rpm to extrude into a sheet with a thickness of about 2-3mm, and then cooled and shaped, and cut into suitable sizes for standby use;

[0071] 2. Preparation of the middle layer: After drying the aluminum hydroxide flame retardant in a vacuum drying oven at 80-90°C for 4-6 hours, melt-blending and extruding it in a twin-screw extruder. The temperature of each section of the extruder is set to 200-210°C, 210-220°C, and 220-230°C. The screw speed is 200-300 rpm to make a sheet with a thickness of about 1-2 mm. After cooling, cut it into a suitable size for standby use;

[0072] 3. Preparation of surface layer: PVC resin, alumina wear-resistant agent, flame retardant, anti-ultraviolet agent, stabilizer additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes according to the proportion to make the materials evenly mixed; the mixed materials are extruded into sheets in an extruder, the extruder temperature is set to 160-170°C, 170-180°C, 180-190°C, the screw speed is 40-60 rpm, the sheet thickness is about 0.5-1mm, cooled and shaped, and cut into suitable sizes for standby use;

[0073] 4. Preparation of the wrapping layer: Dry the TPU particles in a vacuum drying oven at 80-90°C for 4-6 hours, and fully mix the dried TPU particles and ammonium polyphosphate powder in a high-speed mixer according to the ratio. The mixing time is about 10-15 minutes, and the speed is controlled at 800-1200 rpm; add the mixed materials into a twin-screw extruder for melt blending and extrusion granulation. The extrusion temperature is set at 180-220°C and the screw speed is 200-300 rpm to obtain TPU / APP composite material particles; The TPU / APP composite material particles are made into a film with a thickness of about 0.2-0.5 mm by a casting or blow molding process for standby use;

[0074] 5. Floor molding: After the prepared base layer, middle layer and surface layer are stacked in order, they are preliminarily hot-pressed and laminated on a hot press machine. The hot-pressing conditions are temperature 120-150°C, pressure 3-5MPa, and time 2-3 minutes, so that the three layers are tightly combined; the prepared TPU / APP film is covered on the surface of the preliminarily laminated board, and the hot press machine is used again to perform hot-pressing pattern treatment at 130-160°C and pressure 4-6MPa for 3-5 minutes, so that the film is firmly wrapped around the outside of the floor, and at the same time, a decorative and anti-slip pattern is formed to finally obtain the finished product.

[0075] Comparative experiment:

[0076] According to the formula and preparation process in Example 2, Comparative Example 1 and Comparative Example 2, three kinds of flooring were prepared respectively. The flame retardant performance, wear resistance, UV resistance and physical properties of the three kinds of flooring were tested respectively. The specific experimental process and results are as follows:

[0077] 1. Flame retardant performance test

[0078] 1.1 Test Method

[0079] The limiting oxygen index (LOI) test method is used to make the sample into a specimen of a specific size. In a nitrogen-oxygen mixed gas flow, the minimum oxygen concentration required for the sample to just maintain combustion is measured. The LOI value is used as an indicator to evaluate the flame retardant performance. The higher the LOI value, the better the flame retardancy of the material.

[0080] At the same time, observe the burning time and self-extinguishing time of the material in the flame. Ignite the sample under the specified fire source conditions and record the time from ignition to flame extinguishing. The shorter the burning time and the faster the self-extinguishing time, the better the flame retardant performance.

[0081] 1.2 Test Results

[0082] Floor Type LOI Scope Burning time (seconds) Self-extinguishing time (seconds) Example 2 35% 10 5 Comparative Example 1 25% 30 20 Comparative Example 2 27% 25 15

[0083] 2. Wear resistance test

[0084] 2.1 Test Method

[0085] Using the Taber wear tester, a grinding wheel of a certain specification is rotated at a certain speed under a certain load to perform a wear test on the floor surface. After the specified number of wear revolutions, the mass loss of the sample is measured, and the wear resistance of the floor is evaluated by the size of the mass loss. The smaller the mass loss, the better the wear resistance;

[0086] 2.2 Test Results

[0087] Floor Type Wear revolutions Mass loss (g) Example 2 5000 rpm 0.05 Comparative Example 1 5000 rpm 0.12 Comparative Example 2 5000 rpm 0.08

[0088] 3. Anti-ultraviolet performance test

[0089] 3.1 Test Method

[0090] Place the floor sample in a UV aging test chamber and irradiate it continuously for a certain period of time (e.g. 1000 hours) under the specified UV radiation intensity, temperature and humidity conditions. Before and after irradiation, measure the color change (expressed by the color difference value ΔE, the smaller the ΔE, the smaller the color change, the better the UV resistance) and the change rate of mechanical properties (such as tensile strength, bending strength, etc.) of the sample. The smaller the change rate, the better the UV resistance.

[0091] 3.2 Test Results

[0092] Floor Type Color change ΔE Tensile strength change rate Bending strength change rate Example 2 2.5 -5% -3% Comparative Example 1 5.0 -12% -8% Comparative Example 2 3.5 25 -5%

[0093] 4. Physical performance test

[0094] 4.1 Test Method

[0095] For hardness test, a Shore hardness tester is used to select multiple test points on the floor surface, measure their hardness values, and take the average value as the hardness index of the floor;

[0096] Bending strength test: According to GB / T9341-2008 "Determination of Bending Properties of Plastics", the floor samples are made into standard sizes and subjected to a three-point bending test on a universal material testing machine to determine their bending strength;

[0097] Dimensional stability test: place the floor sample in a specified temperature (such as 80°C) and humidity (such as 90% RH) environment for a certain period of time (such as 24 hours), and measure the rate of change of sample size;

[0098] 4.2 Test Results

[0099]

[0100] From the above test data, we can see that:

[0101] In terms of flame retardant performance, the layered structure and reasonable material ratio of Example 2 perform best, with a higher limiting oxygen index, shorter burning time and self-extinguishing time, and each layer of flame retardant can work synergistically to effectively prevent the spread of flames and continuous combustion. Due to the lack of a layered structure in Comparative Example 1, the distribution and synergistic effect of the flame retardant are destroyed, and the flame retardant performance is significantly reduced. After the middle layer of Comparative Example 2 lacks PETG material, the overall flame retardant synergistic effect becomes worse. Although it is slightly better than Comparative Example 1, it is still far less than Example 2, indicating that PETG in the middle layer cooperates with other flame retardants to play a key role in improving the flame retardant performance of the floor;

[0102] In terms of wear resistance, Example 2 has the smallest mass loss and the best wear resistance. Comparative Example 1 has the largest mass loss and the worst wear resistance, which may be because the structure of its overall mixed material is not as conducive to the wear resistance of the anti-wear agent as the layered structure. The wear resistance of Comparative Example 2 is between the two, indicating that PETG material also has a certain influence on the wear resistance, but it is not the only determining factor;

[0103] In terms of anti-ultraviolet performance, Example 2 has the smallest color change and mechanical property change rate, and the best anti-ultraviolet performance. Comparative Example 1 has large changes in color and mechanical properties, and poor anti-ultraviolet performance, which may be due to the material mixing method that makes the anti-ultraviolet agent unable to play an effective role. The anti-ultraviolet performance of Comparative Example 2 is weaker than that of Example 2, which once again proves the positive effect of PETG material in the middle layer on the overall performance of the floor.

[0104] In terms of physical properties, Example 2 performs well in hardness, bending strength and dimensional stability, while Comparative Example 1 is relatively poor in various physical performance indicators, and Comparative Example 2 is between the two. This shows that the layered structure and PETG material also have a certain influence on the physical properties of the floor, and reasonable layered design and material selection are helpful to improve the overall physical properties of the floor;

[0105] In summary, in the design and preparation of flame-retardant SPC flooring, a reasonable layered structure and the use of the key material PETG are crucial to optimizing flame retardant properties. These factors should be given full attention in the actual production and research and development process. At the same time, the actual flame retardant properties need to be further verified and optimized through strict standard tests.

[0106] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.

Claims

1. A flame retardant stone plastic floor, characterized in that: The floor comprises a base layer, an intermediate layer, a surface layer and a covering layer, wherein the intermediate layer is arranged between the base layer and the surface layer, and the covering layer is wrapped around the outside of the base layer, the intermediate layer and the surface layer; The base layer comprises 60-70 parts of polyvinyl chloride resin, 200-250 parts of calcium carbonate powder, 3-5 parts of stabilizer, and 1-2 parts of lubricant; The middle layer contains 70-80 parts of non-crystalline copolyester and 20-30 parts of aluminum hydroxide flame retardant; The surface layer comprises 70-80 parts of polyvinyl chloride resin, 10-15 parts of alumina wear-resistant agent, 5-8 parts of flame retardant, 1-2 parts of anti-ultraviolet agent, and 3-5 parts of stabilizer; The coating layer contains 70-80 parts of thermoplastic polyurethane elastomer rubber and 20-30 parts of ammonium polyphosphate.

2. The flame retardant stone plastic floor as claimed in claim 1, characterized in that: The stabilizer is a calcium zinc stabilizer, the lubricant is stearic acid, the flame retardant is antimony trioxide, and the anti-ultraviolet agent is benzotriazole.

3. A method for preparing a flame retardant stone plastic floor, characterized in that: A flame-retardant stone plastic flooring as described in any one of claims 1-2, comprising the following method steps: Step 1: Base layer preparation: The PVC resin, calcium carbonate powder, stabilizer and lubricant additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes according to the above ratio to make the materials evenly mixed; Add the mixed materials into a single-screw or twin-screw extruder, set the temperature of each section of the extruder to 150-160°C, 160-170°C, 170-180°C, and control the screw speed at 30-50 rpm to extrude into sheets with a thickness of about 2-3mm, then cool and shape, and cut into suitable sizes for later use; Step 2: Preparation of the intermediate layer: After drying the PETG particles and the aluminum hydroxide flame retardant in a vacuum drying oven at 80-90°C for 4-6 hours, the PETG particles and the aluminum hydroxide flame retardant are melt-blended and extruded in a twin-screw extruder. The temperature of each section of the extruder is set to 200-210°C, 210-220°C, and 220-230°C. The screw speed is 200-300 rpm to form a sheet with a thickness of about 1-2 mm. After cooling, the sheet is cut into a suitable size for standby use. Step 3: Surface preparation: The PVC resin, aluminum oxide wear-resistant agent, flame retardant, UV-resistant agent, stabilizer additive are fully mixed in a high-speed mixer at a speed of 800-1000 rpm for 10-15 minutes to make the materials evenly mixed; The mixed material is extruded into a sheet in an extruder, the extruder temperature is set to 160-170°C, 170-180°C, 180-190°C, the screw speed is 40-60 rpm, the sheet thickness is about 0.5-1mm, cooled and shaped, and cut into suitable sizes for use; Step 4: Preparation of wrapping layer: Dry the TPU pellets in a vacuum drying oven at 80-90°C for 4-6 hours; The dried TPU particles and ammonium polyphosphate powder are fully mixed in a high-speed mixer according to the ratio. The mixing time is about 10-15 minutes, and the speed is controlled at 800-1200 rpm; The mixed materials are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion temperature is set at 180-220°C, and the screw speed is 200-300 rpm to obtain TPU / APP composite material particles; The TPU / APP composite material particles are made into a film with a thickness of about 0.2-0.5 mm by a casting or blow molding process for later use; Step 5: Floor molding: After the prepared base layer, middle layer and surface layer are stacked in order, they are preliminarily hot-pressed and laminated on a hot press machine. The hot-pressing conditions are temperature 120-150°C, pressure 3-5MPa, and time 2-3 minutes, so that the three layers are tightly combined; The prepared TPU / APP film is covered on the surface of the preliminarily compounded board, and then the pattern is hot-pressed again by a hot press at 130-160°C and a pressure of 4-6MPa for 3-5 minutes, so that the film is firmly wrapped around the outside of the floor, and a decorative and anti-slip pattern is formed, and finally a flame-retardant stone plastic floor product is obtained.

Citation Information

Patent Citations

  • Stone-plastic floor and preparation method thereof

    CN109057241A

  • Flame-retardant fireproof laminate floor and preparation method thereof

    CN112502383A

  • Multilayer co-extruded stone-plastic floor and manufacturing method thereof

    CN112746719A

  • Low-smoke flame-retardant base film for environment-friendly floor leather surface layer and preparation method of low-smoke flame-retardant base film

    CN116082825A

  • Plastic floor for ship and processing method

    CN118306090A